Factors that influence user satisfaction with campus spaces: a comparative study of design-based and non-design based classroom - Hashim, Hasnan; Ramlan, Muhammad Ruzaini; Samsul Rijal, Nurhidayah; Abd Rased, An Nisha Nur Welliana (Universiti Teknologi MARA, Perak, 2025)
Space management is an effective management of space utilisation aimed at reducing the cost and wastage of spaces. The aim of this study is to improve the space management practices at College of Built Environment (CBE), UiTM, Shah Alam. The finding is hoped to benefit the Space Management Unit, Facilities Management Office who is in charge of the space management for CBE. In order to achieve the research aim, three objectives have been set out. The objectives were to investigate the current practices of space management at CBE’s Building, to identify the space requirement at CBE’s faculty and to identify the level of user satisfaction on space management at CBE’s Building. The methodology adopted was qualitative and quantitative method using literature review, semi-structured interview and questionnaire survey. SPSS version 20 was used to analyse the data. The results revealed that the practices of space management were traditional and not centralise, the types of space required by the faculty includes classroom, computer laboratory, TEC room, workshop (timber laboratory and concrete laboratory), studio, lecture hall and external study area.